2014
DOI: 10.1038/ncomms4292
|View full text |Cite
|
Sign up to set email alerts
|

HDL-transferred microRNA-223 regulates ICAM-1 expression in endothelial cells

Abstract: High-density lipoproteins (HDL) have many biological functions, including reducing endothelial activation and adhesion molecule expression. We recently reported that HDL transport and deliver functional microRNAs (miRNA). Here we show that HDL suppresses expression of intercellular adhesion molecule 1 (ICAM-1) through the transfer of miR-223 to endothelial cells. After incubation of endothelial cells with HDL, mature miR-223 levels are significantly increased in endothelial cells and decreased on HDL. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
313
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(331 citation statements)
references
References 70 publications
(75 reference statements)
9
313
0
1
Order By: Relevance
“…120 HDL was shown to deliver miR-223 into endothelial cells, where it downregulates expression of intracellular cell adhesion molecule 1 (ICAM-1). 121 However, these findings are in contrast to those by Wagner et al 10 who confirmed the presence of low copy numbers of miRNAs in HDL, but found no evidence that HDL delivers physiologically relevant amounts of miRNAs into endothelial cells, smooth muscle cells, and peripheral blood mononuclear cells. 10 In general, it is important to emphasize the low concentration of miRNAs in HDL, which is beyond particle concentration.…”
Section: Sphingolipidsmentioning
confidence: 68%
“…120 HDL was shown to deliver miR-223 into endothelial cells, where it downregulates expression of intracellular cell adhesion molecule 1 (ICAM-1). 121 However, these findings are in contrast to those by Wagner et al 10 who confirmed the presence of low copy numbers of miRNAs in HDL, but found no evidence that HDL delivers physiologically relevant amounts of miRNAs into endothelial cells, smooth muscle cells, and peripheral blood mononuclear cells. 10 In general, it is important to emphasize the low concentration of miRNAs in HDL, which is beyond particle concentration.…”
Section: Sphingolipidsmentioning
confidence: 68%
“…Population studies elucidated HDLs as an independent inverse predictor of cardiovascular disease 30, 31. These epidemiologic findings were confirmed in vitro and in animal models, as supported by promotion of cholesterol efflux from cells or tissues,32 inhibition of vascular inflammation33, and improved endothelial cell function 34. Whereas most studies reported the relationship between circulating ANGPTL4 levels and HDL‐c, they mainly recruited Europeans,8, 14 American,12 or Hispanic subjects 35.…”
Section: Discussionmentioning
confidence: 85%
“…Tabet et al . (2014) demonstrated that miR‐223 is transferred from native HDL to endothelial cells and HDL inhibits expression of intercellular adhesion molecule 1 (ICAM‐1) through the transfer of miR‐223 to endothelial cells. All these findings support that HDL‐miRNA delivery is a new mechanism of miRNA transport.…”
Section: How Cells Communicatementioning
confidence: 99%